2010
DOI: 10.1111/j.1532-849x.2009.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Denture Cleansing Solutions on the Retention of Pink Locator Attachments: An in Vitro Study

Abstract: Cool Mint Listerine and Efferdent's small effect on the retentive values of the Locators might be clinically unimportant; however, NaOCl caused a large reduction in the retentive values of the attachments. Because of their effect on retentive values and on the color of the Locator attachments, NaOCl and Cool Mint Listerine are not recommended. These results should be interpreted clinically with caution, realizing that different results may be obtained when fatigue stress during function and multiple pulls (in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
122
3
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(144 citation statements)
references
References 17 publications
10
122
3
9
Order By: Relevance
“…A similar observation was also noted in another study . The lower vertical height of the Locator attachment (2.5 mm) could be responsible for the minimal resistance of the Locator attachment to lateral dislodging forces . In line with this finding, Rutkunas et al reported that Locators showed the best retention during posterior rotational dislodgement.…”
Section: Discussionsupporting
confidence: 79%
“…A similar observation was also noted in another study . The lower vertical height of the Locator attachment (2.5 mm) could be responsible for the minimal resistance of the Locator attachment to lateral dislodging forces . In line with this finding, Rutkunas et al reported that Locators showed the best retention during posterior rotational dislodgement.…”
Section: Discussionsupporting
confidence: 79%
“…It became more popular in the last decade as an attachment for free‐standing implants supporting overdentures . Compared to other unsplinted attachments, locators have: (i) low profile (can be used in a limited interarch distance) , (ii) dual retention (obtained from the inner and outer contact surfaces between matrices and patrices and (iii) higher retentive force . Moreover, these attachments are self‐aligning , can compensate for up to 40◦ implant disparallelism and can be easily repaired and replaced .…”
Section: Introductionmentioning
confidence: 99%
“…Standard cleansing procedures are always necessary for the care of removable prostheses, regardless of the attachment types . Poor hygiene results in plaque accumulation with inflammatory changes and malodor.…”
mentioning
confidence: 99%
“…Daily denture‐brushing is recommended for all denture‐wearers, but alone, it is not sufficient for hygiene precautions and therefore daily care should include soaking the dentures in a chemical solution . Alkaline peroxide solutions are widely used cleansers that remove debris due to their mechanical effervescing action.…”
mentioning
confidence: 99%